Indigenous Knowledge for Development - Mohan, P.C. (World Bank, Washington, DC, 2012)
The Indigenous Knowledge for Development Program, started in 1998, was the Bank's response to clients, and civil society who called for a more systematic integration of the indigenous knowledge (IK) in the development process. The program developed partnerships, and collaborative links with mostly nongovernmental organizations-operated IK resource centers in Africa, and, its objectives include raising awareness about the potential use of IK in development, disseminating pertinent information, and integrating IK into Bank projects, and capacity building of local institutions. The note reviews the impact on the ground of Bank projects, of research cooperation between NGOs, and/or other institutions on medicinal plants, of sharing environmental management programs, and of information exchange and dissemination. Lessons address the need to recognize IK existing trends, and institutionalize selectively, while seeking partnerships to foster the process with a national, local, and institutional official support. Moreover, lessons stress the need for wider stakeholder involvement, to pursue, and enrich the development process.